Physical illness and dementia among the elderly patients in a tertiary care hospital: a cross sectional study (Bangladesh Journal of Psychiatry, 2020)
The elder people are rapidly increasing throughout the world and dementia has become the important point of interest of health care professionals. The objective of the study was to find out the physical illness and dementia as well as their association among the elderly patients. This was a cross sectional and analytical study conducted in National Institute of Mental Health (NIMH) at Sher-e-Bangla Nagar, Dhaka, Bangladesh during the period from 1st November 2014 to 30th April 2015. For this purpose 78 elderly patients aged e”60 years attending both in outpatient and inpatient department of NIMH satisfying inclusion and exclusion criteria, irrespective of age and gender were selected as study population by convenient sampling technique. The result showed that majority (59%) had co-morbid physical illness. Common co-morbid physical illness was hypertension (26.9%). Among the respondants, 5 (6.4%) were current smokers and 12 (15.38%) had past history of smoking for more than five years. In the study, 50% of the respondents diagnosed with dementia had hypertension (c2 = 3.8808, P= 0.04884), 25% dementia patient had co-morbid diabetes mellitus (c2 = 2.4287, P= 0.11913), history of cerebro vascular accident (CVA) was present in 25% of patient and 25% patient had history of smoking (c2 = 0.0088, P= 0.92533). This study provided baseline information about clinical factors associated with dementic patients in Bangladesh which could be used in future studies.Bang J Psychiatry June 2017; 31(1): 20-23